Sense of coherence and social support as predictors of mental health during COVID-19 pandemic - Fabiane Dolphine Fuentes Penachiotti; Mirian Ueda Yamaguchi; Adi Mana; Shifra Sagy; Rute Grossi-Milani (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objectives: to verify the role of sense of coherence, sense of national coherence, social support and trust in institutions to predict mental health in Brazilians during the COVID-19 pandemic. Methods: a cross-sectional study, carried out from November, 2020 to January, 2021 via an online survey. Standardized instruments were used. The sample consisted of 1,630 Brazilians. Pearson's correlation and linear regression were performed in data analysis. Results: sense of coherence was the only predictor of anxiety [β= -0.61; p<0.001], explaining 38% of the variance in its scores, while sense of coherence [β= 0.52; p<0.001], sense of national coherence [β= 0.16; p<0.001], and social support [β= 0.15; p<0.001] predicted positive mental health and together explained 51% of its variance. Conclusions: the findings suggest that sense of coherence, sense of national coherence and social support represent important predictors for mental health and that strengthening these resources, could potentially promote Brazilians' mental health.